PENGARUH MEDIA PEMBELAJARAN WAYANG KERTAS TERHADAP NILAI KARAKTER SISWA SEKOLAH DASAR - Erwin Putera Permana (Program Studi PGSD Universitas Flores, 2021)
Indonesia has abundant cultural diversity. Each region has its own cultural characteristics. Currently, elementary school students' love for art has begun to fade, even though there are so many arts developing. By modifying the puppets into paper puppets, it is easy to make and use them as learning media. Elementary school is a fundamental and strategic education, because it is a golden period and laying the foundation for child development. In addition, the environment plays a very large role in the formation of attitudes and children, namely character. Character is a characteristic that is attached to a person, manifested through moral values and then becomes the hallmark of a person who is formed in life. The purpose of this study was to prove the effect of the application of paper puppet learning media on the character values of elementary school students. The type of research used is experimental research with one-group pretest posttest design technique. The results of the study using paper puppet learning media made students' character values stronger. This can be seen from the average value before being given treatment, the results are 92.63 while after being given treatment the results are 160.72. Based on the analysis of paired sample t-test data, it is known that Sig. (2-tailed) is 0.000 <0.05, in general it can be concluded that there is an effect of the application of the Paper Puppet Learning Media on the Character Values of Elementary School Students.